Prioritizing Parkinson’s disease risk genes in genome-wide association loci - Lara M. Lange; Catalina Cerquera-Cleves; Marijn Schipper; Georgia Panagiotaropoulou; Alice Braun; Julia Kraft; Swapnil Awasthi; Nathaniel Bell; Danielle Posthuma; Stephan Ripke; Cornelis Blauwendraat; Karl Heilbron (npj Parkinson's Disease)
Abstract Many drug targets in ongoing Parkinson’s disease (PD) clinical trials have strong genetic links. While genome-wide association studies (GWAS) nominate regions associated with disease, pinpointing causal genes is challenging. Our aim was to prioritize additional druggable genes underlying PD GWAS signals. The polygenic priority score (PoPS) integrates genome-wide information from MAGMA gene-level associations and over 57,000 gene-level features. We applied PoPS to East Asian and European PD GWAS data and prioritized genes based on PoPS, distance to the GWAS signal, and non-synonymous credible set variants. We prioritized 46 genes, including well-established PD genes (SNCA, LRRK2, GBA1, TMEM175, VPS13C), genes with strong literature evidence supporting a mechanistic link to PD (RIT2, BAG3, SCARB2, FYN, DYRK1A, NOD2, CTSB, SV2C, ITPKB), and genes relatively unexplored in PD. Many hold potential for drug repurposing or development. We prioritized high-confidence genes with strong links to PD pathogenesis that may represent our next-best candidates for developing disease-modifying therapeutics.